A birth cohort study of Asian and Pacific Islander children reported for abuse or neglect by maternal nativity and ethnic origin. (October 2017) - Finno-Velasquez, Megan; Palmer, Lindsey; Prindle, John; Tam, Christina C.; Putnam-Hornstein, Emily
Abstract: Research identifying racial and ethnic disparities in child protective services (CPS) involvement in the U.S. has focused on the overrepresentation of Black children and the growing Latino child population. Little attention has been paid to children of Asian origin, the most underrepresented group of children in the U.S. CPS system. The objective of this analysis was to examine subgroup patterns of CPS involvement in California for Asian and Pacific Islander (API) children prospectively based on maternal nativity and ethnic origin. We extracted data for API children born in California in 2006 and 2007 ( N  = 138, 858) from population-based birth records and linked those records to CPS records spanning the first 5 years of life (through 2012). We assessed distributional differences in risk indicators for the full birth cohort of API children and calculated a summary risk variable representing the cumulative number of risks present at birth. Generalized linear models were used to estimate API children's adjusted relative risk of CPS report by subgroup. Overall, 12.2% of children born in California in the 2006–2007 birth cohort were API. The majority of API children had foreign-born mothers (80.9%). Children of U.S.-born Hawaiian, Guamanian, or Samoan mothers had the highest rate, with 20.4% being reported to CPS by their 5th birthday. The lowest rates of child abuse and neglect reporting were observed among children of foreign-born Asian Indian (2.5%), Korean (2.7%), and Chinese (2.8%) mothers, compared to 5.4% of all Asian and Pacific Islander children, and 14.8% of children in general population. Findings underscore the presence of disparities in CPS involvement among API children, which has implications for health and well-being across the life course and for targeted maltreatment prevention strategies.